2016
DOI: 10.1080/19443994.2015.1040850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic substances on struvite crystallization and recovery

Abstract: A B S T R A C TThe effects of organic substances on struvite crystallization and recovery from synthetic wastewater were investigated. Experiments were completed during trials lasting 5 days using a pilot reactor with two concentric stainless steel meshes as seed material. Various concentrations of organics were added to synthetic CO 2 -saturated solutions and the pH was elevated from an initial value of 6.5 using a degassing technique. The results showed the presence of glucose, humic acid, and citric acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…The presence of bio-struvite was confirmed with energy-dispersive X-ray spectroscopy. The spectra obtained matched the spectra expected for struvite crystals (Figure 4d), and the morphology of the bio-struvite crystals, observed in the electron microscope, was found to follow characteristic prismatic, tabular, and twinnedcrystal habit (Figure 4) similar to the morphologies found in other published reports on struvite [7,[29][30][31].…”
Section: Bio-struvite Productionsupporting
confidence: 85%
See 1 more Smart Citation
“…The presence of bio-struvite was confirmed with energy-dispersive X-ray spectroscopy. The spectra obtained matched the spectra expected for struvite crystals (Figure 4d), and the morphology of the bio-struvite crystals, observed in the electron microscope, was found to follow characteristic prismatic, tabular, and twinnedcrystal habit (Figure 4) similar to the morphologies found in other published reports on struvite [7,[29][30][31].…”
Section: Bio-struvite Productionsupporting
confidence: 85%
“…Organic substances as humic and citric acids have been shown to inhibit struvite formation [29,30]. And acetate has been reported to delay the precipitation of struvite at more than 5 mM (equiv.…”
Section: Bio-struvite Productionmentioning
confidence: 99%
“…Fig. 7b shows 10 -5 ) [38,42], respectively, which is unfavorable to the reaction of struvite crystallization. ValsamiJones [43] reported that the organic acids could be adsorbed onto the crystal nucleus of struvite, blocking the subsequent growth of struvite crystals and increasing the required supersaturation index for struvite crystallization, which would lead to a decrease of the nutrients removal efficiency.…”
Section: Effect Of Solution Phmentioning
confidence: 96%
“…The molar relation between metal ions and phosphate in the HTL solid phase from SPR (Al/P~0.03 and Fe/P~0.07) was lower than that from PSS (Al/P~0.21 and Fe/P~0.08), which can result in less co-precipitation of secondary Al-and Fe-phosphate salts [77]. While citric acid provided a high extraction capacity for HTL-SPR-SP, its application may be limited by its negative effect on subsequent precipitation [79]. Figure 4a conveys that sulfuric acid is more selective to phosphate release compared to other leaching agents.…”
Section: Phosphate Recoverymentioning
confidence: 98%